2007
DOI: 10.3892/ijo.30.5.1059
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of genetic alteration patterns in human esophageal squamous cell carcinoma using selected microsatellite markers spanning multiple loci

Abstract: In order to identify representative genetic alterations in esophageal squamous cell carcinomas (ESCC) and useful markers for future early detection, 34 ESCC samples with neighboring normal epithelia and 30 esophageal biopsy samples from Linzhou, P.R. China, were studied. Of the 38 microsatellite markers selected, half were linked with tumor suppressors. More than 40% of the tumor samples showed loss of heterozygosity (LOH) in at least one of the eight markers, D3S1067 and D3S1561 (both linked to hMLH1 locus), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…In our study 27, 25 and 36% of 40 Iranian patients with esophageal cancer showed LOH at the D5S1384, D5S1478 and D5S1505 markers, respectively. It was suggested that LOH with less than 22% incidence for a marker could be regarded as a non-specific event (Cai et al, 2007). Thus, the deletions we observed were not random occurrences and a TSG(s) is/are probably located near the region studied.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In our study 27, 25 and 36% of 40 Iranian patients with esophageal cancer showed LOH at the D5S1384, D5S1478 and D5S1505 markers, respectively. It was suggested that LOH with less than 22% incidence for a marker could be regarded as a non-specific event (Cai et al, 2007). Thus, the deletions we observed were not random occurrences and a TSG(s) is/are probably located near the region studied.…”
Section: Discussionmentioning
confidence: 78%
“…It is reported that MSI occurs frequently in Barrett'sassociated EAC, but not in ESCC (Meltzer et al, 1994). Additionally, there is evidence implying an inverse relationship between LOH and MSI in other cancers (Cai et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…EC has a high incidence in people between 60 years and 64 years, and its incidence shows a gradual decrease in people over 70 years. In addition, EC presents a characteristic of noticeable geographic aggregation in China: High-incidence and -mortality areas quite concentrate, especially in the north of Henan Province near Taihang Mountains where the average mortality rate is 14.59/100,000, ranking fourth among various malignancies (Cai et al, 2007). Furthermore, EC has a general higher incidence in countrysides than in cities.…”
Section: Introductionmentioning
confidence: 99%
“…Qualitatively, both MI in nDNA and heteroplasmic/homoplasmic mutation in mtDNA suggest the formation of new shifted DNA. Microsatellite markers, including mononucleotide poly-C repeats on mtDNA (e.g., D310) or dinucleotide CA repeat on nDNA close to TP53 (e.g., D17S960) have been analyzed in TESCC, however, their roles and associations in TESCC have remained obscure (6,(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%